The Human Antimicrobial Peptides Dermcidin and LL-37 Show Novel Distinct Pathways in Membrane Interactions - Zeth, Kornelius; Sancho-Vaello, Enea (Frontiers in Chemistry, 2017)
Mammals protect themselves from inflammation triggered by microorganisms through secretion of antimicrobial peptides (AMPs). One mechanism by which AMPs kill bacterial cells is to perforate their membranes. Membrane interactions and pore formation were investigated for -helical AMPs leading into the formulation of three basic mechanistic models: the barrel stave, toroidal and carpet model. One major drawback of these models is their simplicity not reflecting the real in vitro and in vivo conditions. To challenge and refine these models using a structure-based approach we set out to investigate how human cathelicidin (LL-37) and dermcidin (DCD) interact with membranes. Both peptides are -helical and their structures have been solved at atomic resolution. DCD assembles in solution into a hexameric pre-channel complex before the actual membrane targeting and integration step can occur and the complex follows a deviation of the barrel stave model. LL-37 interacts with lipids and shows the formation of oligomers generating fibril-like supramolecular structures on membranes. LL-37 further assembles into transmembrane pores with yet unknown structure expressing a deviation of the toroidal pore model. Both of their specific targeting mechanisms will be discussed in the context of the ‘old’ models propagated in the literature.